Signaling Potential Therapeutic Herbal Medicine Prescription for Treating COVID-19 by Collaborative Filtering - Yang, Fan; Zhang, Qi; Yuan, Zhongshang; Teng, Saisai; Cui, Lizhen; Xue, Fuzhong; Wei, Leyi (Frontiers in Pharmacology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has aggressed more than 200 countries and territories since Dec. 2019, and have reported 30 million cases of coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2, including 950,000 deaths. Supportive treatment remains the mainstay of therapy for COVID-19. Supportive treatment remains the mainstay of therapy for COVID-19. There are no small-molecule specific anti-viral drugs are available to prevent and treat COVID-19 up to lately. Herbal medicine can facilitate syndrome differentiation and treatment according to the clinical manifestations of patients and has demonstrated effectiveness in epidemic prevention and control. The National Health Commission (NHC) of China has recommended “Three TCM prescriptions and three medicines”, as a group of six effective herbal formulae against COVID‑19 in the released official file Diagnosis and Treatment Protocol for COVID-19 Patients Herbal Medicine for the Priority Treatment of COVID‑19. This paper aims to developing a collaborative filtering approach to signaling drug-combinations that similar to the six herbal formulae as the potential therapeutic treatments for treating COVID-19. And the results have been evaluated by herbal medicine experts’ domain knowledge.